A Cultural Analysis of Religious, Heroic, and Social Values in Ten Poems of Abdullah ibn Rawahah during the Early Islamic Period - Muhammad Regi Iswara Putra; R. Myrna Nur Sakinah (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This study examines the religious, heroic, and social values reflected in ten selected poems of Abdullah ibn Rawahah, one of the most prominent poets and companions of Prophet Muhammad SAW during the early Islamic period. The poems analyzed include verses concerning faith in Allah, praise of the Prophet Muhammad, the Battle of Mu'tah, courage, jihad, truth, steadfastness, and martyrdom. Employing a cultural approach and a qualitative descriptive method, this research investigates how these poems represent the cultural identity and worldview of the early Muslim community. The findings reveal that Abdullah ibn Rawahah’s poetry emphasizes four dominant cultural values: religious devotion, heroism, social solidarity, and Islamic identity. His poems portray unwavering faith in Allah, loyalty to the Prophet, courage in facing death, and commitment to defending Islamic teachings. Furthermore, the poems demonstrate the transformation of Arabic literary traditions from tribal-centered expressions into literary instruments that promoted religious and moral values. The influence of Qur’anic teachings is also evident in the themes and language of the poems. This study concludes that Abdullah ibn Rawahah’s poetry played a significant role in shaping the cultural consciousness of early Islamic society and served as an effective medium for transmitting religious, ethical, and social values.